Macrophages as a source and target of GDF-15 - Silva Bermudez, Lina Susana; Klüter, Harald; Kzhyshkowska, Julia (International journal of molecular sciences, 2024)
Growth differentiation factor 15 (GDF-15) is a multifunctional cytokine that belongs to the transforming growth factor-beta (TGF-β) superfamily. GDF-15 is involved in immune tolerance and is elevated in several acute and chronic stress conditions, often correlating with disease severity and patient prognosis in cancer172 and metabolic and cardiovascular disorders. Despite these clinical associations, the molecular mechanisms orchestrating its effects remain to be elucidated. The effects of GDF-15 are pleiotropic but cell-specific and dependent on the microenvironment. While GDF-15 expression can be stimulated by inflammatory mediators, its predominant effects were reported as anti-inflammatory and pro-fibrotic. The role of GDF-15 in the macrophage system has been increasingly investigated in recent years. Macrophages produce high levels of GDF-15 during oxidative and lysosomal stress, which can lead to fibrogenesis and angiogenesis at the tissue level. At the same time, macrophages can respond to GDF-15 by switching their phenotype to a tolerogenic one. Several GDF-15-based therapies are under development, including GDF-15 analogs/mimetics and GDF-15-targeting monoclonal antibodies. In this review, we summarize the major physiological and pathological contexts in which GDF-15 interacts with macrophages. We also discuss the major challenges and future perspectives in the therapeutic translation of GDF-15.